The Description of Students’ Problem in Learning Vocabulary through Flash Card at Tenth Grade of SMK Negeri 1 Tuhemberua in 2022/2023 - Otomosi Gea; Yasminar A. Telaumbanua; Adieli Laoli; Nursayani Maru’ao (Journal on Education, 2023)
In learning process that occurred at the tenth grade of SMK Negeri 1 Tuhemberua, the students need to master vocabulary in English learning. Therefore, the objectives of this research were to describe how the teacher applies flash card to teach vocabulary to the students and to find out the students’ problem in learning vocabulary through flash card at tenth grade of SMK Negeri 1 Tuhemberua in 2022/2023. The method used in this research was descriptive qualitative. Data were obtained from observation sheet and field notes which were then analyzed using after the lecturer used flash card by the English teacher and from interviews for tenth grade students and English teacher. The results showed that students’ problem was the type of interaction carried out during the English learning process and the students still do not have connotation and collocation as good as possible in daily life. Therefore they need good method to encourage them to study effectively. Furthermore, the influencing factors are the students still dislike learning vocabulary; they responded that they just study vocabulary when the time of English course takes place in the class.